Introduction - Panieri, Giuliana; Stiller-Reeve, Mathew (Septentrio Educational, 2023)
An introduction to the 16 interdisciplinary lesson plans and ideas about the ocean and connecting to it via the senses that make up this booklet. The booklet was developed as part of the Advancing Knowledge about Methane in the Arctic (AKMA) Project, which is also briefly presented here.